DECISION MAKING IN MEDICO-LEGAL OPINION - kumar, Arvind; Kumar, Mahesh; Singh, Sukhdeep (Journal of Forensic Medicine and Toxicology, 2018)
Opinion expression is an important part of medico- legal writing. Recent judgment on Criminal Appeal No529  of 2010 has highlighted the importance of Investigating Officer and Medical Officer in criminal cases. This paper discusses many types of opinion and their critical analysis. The physician should provide reasons for the basis of the opinion.
Keywords: Medicolegal opinion; Decision making Subjectivity; Third party review; Typology of opinion